Letter to Jane Tolmach from Assemblyman Alan Sieroty - Alan Sieroty:::::: (1976)
In a June 11, 1976 letter, Assemblyman Alan Sieroty congratulated Jane Tolmach on her primary victory. He expressed his pleasure at her success and extended best wishes for the upcoming November general election.